2012
DOI: 10.1016/j.molcel.2012.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Mechanistic Principles of a Secondary Multidrug Efflux Protein

Abstract: SUMMARY Multidrug transporters are ubiquitous efflux pumps that provide cells with defense against various toxic compounds. In bacteria, which typically harbor numerous multidrug transporter genes, the majority function as secondary multidrug/proton antiporters. Proton-coupled secondary transport is a fundamental process that is not fully understood, largely owing to the obscure nature of proton-transporter interactions. Here we analyzed the substrate/proton coupling mechanism in MdfA, a model multidrug/ proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
137
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(146 citation statements)
references
References 35 publications
(73 reference statements)
8
137
1
Order By: Relevance
“…MdfA from E. coli serves as a model for secondary Mdr transporters of the MFS (7). This transporter exchanges one proton for one monocationic drug molecule, and the protonatable residue in MdfA has recently been identified (D34) (16). This study also revealed that E26 is essential for D34 deprotonation during the antiport cycle.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…MdfA from E. coli serves as a model for secondary Mdr transporters of the MFS (7). This transporter exchanges one proton for one monocationic drug molecule, and the protonatable residue in MdfA has recently been identified (D34) (16). This study also revealed that E26 is essential for D34 deprotonation during the antiport cycle.…”
Section: Discussionmentioning
confidence: 71%
“…The hypothetical 3D model of MdfA (12) reveals two membrane-embedded negative charges, Glu26 and Asp34 (Fig. 1), which were previously found to be essential for transport of monovalent cationic substrates (13)(14)(15) and interaction with protons (16). Interestingly, unlike several other Mdr transporters, such as LmrP (17), QacA (18), or EmrE (19), the substrate profile of MdfA does not include divalent cations.…”
mentioning
confidence: 92%
“…Such membrane acidic amino acids are found in many proton-dependent transporters belonging to several different families (14)(15)(16)(17)(18). We have recently shown that DedA proteins require these acidic amino acids for the ability to complement the phenotypes of BC202 described above, suggesting they may represent a new family of proton-dependent transporters (12).…”
mentioning
confidence: 93%
“…MdfA is important for substrate but not proton binding (61). MdfA has a 1:1 H ϩ to substrate stoichiometry, and D34 is suggested to be the proton-binding site, indicating an indirect competition mechanism in which protonation of Glu-6 affects the protonation state of Asp-34.…”
Section: H]mppmentioning
confidence: 97%